Brain vitamin D3-auto/paracrine system in relation to structural, neurophysiological, and behavioral disturbances associated with glucocorticoid-induced neurotoxicity - Lisakovska, Olha; Labudzynskyi, Dmytro; Khomenko, Anna; Isaev, Dmytro; Savotchenko, Alina; Kasatkina, Ludmila; Savosko, Serhii; Veliky, Mykola; Shymanskyi, Ihor (Frontiers in Cellular Neuroscience, 2023)
Vitamin D3 (VD3) is a potent para/autocrine regulator and neurosteroid that can strongly influence nerve cell function and counteract the negative effects of glucocorticoid (GC) therapy. The aim of the study was to reveal the relationship between VD3 status and behavioral, structural-functional and molecular changes associated with GC-induced neurotoxicity. There was no difference in open field test (OFT), while forced swim test (FST) showed an increase in immobility time and a decrease in active behavior in prednisolone-treated rats (5 mg/kg b.w., 30 days), indicative of depressive changes. No differences were found in the cytoarchitectonics of the cerebral cortex and thalamus. However, prednisolone increased the perikaryon area, enlarged the size of the nuclei, and caused a slight reduction of cell density in CA1-CA3 hippocampal sections. We established a GC-induced decrease in the long-term potentiation (LTP) in CA1-CA3 hippocampal synapses, the amplitude of high K+-stimulated exocytosis, and the rate of Ca2+-dependent fusion of synaptic vesicles with synaptic plasma membranes. These changes were accompanied by an increase in nitration and ribosylation of cerebral proteins, suggesting the development of oxidative-nitrosative stress. Prednisolone upregulated the expression and phosphorylation of NF-κB p65 subunit at Ser311, whereas downregulating IκB expression. GC loading depleted the circulating pool of 25OHD3 in serum and CSF, elevated VDR mRNA and protein levels but had an inhibitory effect on CYP24A1 and VDBP expression. Vitamin D3 supplementation (1000 IU/kg b.w., 30 days) had an antidepressant-like effect, decreasing the immobility time and stimulating active behavior. VD3 caused a decrease in the size of the perikaryon and nucleus in CA1 hippocampal area. We found a recovery in depolarization-induced fusion of synaptic vesicles and long-term synaptic plasticity after VD3 treatment. VD3 diminished the intensity of oxidative-nitrosative stress, and suppressed the NF-κB activation. Its ameliorative effect on prednisolone-induced neuroanatomical and behavioral abnormalities was accompanied by the 25OHD3 repletion and partial restoration of the VD3-auto/paracrine system. In conclusion, prednisolone-induced neurotoxicity and behavioral disturbances are associated with increased oxidative-nitrosative stress and impairments of VD3 metabolism. Thus, VD3 can be effective in preventing structural and functional disturbances in the brain and behavior changes caused by long-term GC administration.